Modeling Microfinance Acceptance among Social Network Women Entrepreneurs - Ali, Azwadi; Jamaludin, Nurasyikin; Othman, Zatul H. (International Journal of Economics and Financial Issues, 2016)
A pilot study was performed to examine a proposed research model in assessing the determinants of the level of awareness and readiness towards applying for microfinance among social network women entrepreneurs in Malaysia. It was deemed necessary to evaluate the reliability of the proposed measures as well as to form an expectation of the viability of the model. 48 usable responses from pre-identified online female entrepreneurs were gathered from an online survey. The confirmatory factor analysis and reliability test were performed to assess the measures’ loadings, while the model was examined via Partial Least Squares analysis to deduce the potential relationships among the proposed variables. Only a few of the proposed measures were found to have low loadings, and these were modified accordingly, while the proposed variables demonstrated acceptable reliability alpha values. Among the pre-identified antecedents of attitude towards microfinance, subjective norm was found to exhibit the strongest effect among only three significant antecedents. The attitude then explains the level of intention reliably to apply for microfinance. The actual study intends to collect at least 500 responses from women entrepreneurs who are conducting online businesses on social media. Keywords: Microfinance, social network, women entrepreneurs JEL Classifications: A130, O330, D140